Sustainable Digitalization in Public Institutions: Challenges for Human Rights - Pūraitė, Aurelija; Adamonienė, Rūta; Žemeckė, Audronė (European Journal of Sustainable Development, 2020)
The modern world is bound not only by global flows of information, capital, services, and movement of goods and people but also by the wide range of opportunities to exert both positive and negative effects on these flows. Already, most of the aforementioned global flows, stationary and variable objects are protected (organized, coordinated, controlled) by digital technology and in the foreseeable future digitization will encompass the most diverse aspects and processes of existence. Access to the development, deployment, management and use of relevant digital technologies has expanded to such an extent that it has become virtually difficult and even impossible to provide timely protection against a wide range of actors, ranging from unauthorized specialized gathering to varying degrees of security. The development of information technology, which increasingly embraces various aspects of the existence of different security entities, calls for a new rethink of the philosophical - ideological, political, economic, social and cultural foundations of public security. In recent decades human rights have dominated in the discourse of legal and political systems. Now the balance between protection of human rights and public safety in the context of digitalization imposes necessity to reflect the concept of fundamental rights once again. Keywords: Sustainable digitalization, public and private security, human rights